2014
DOI: 10.1364/oe.22.009073
|View full text |Cite
|
Sign up to set email alerts
|

A 10 × 10 Gb/s DFB laser diode array fabricated using a SAG technique

Abstract: We present a ten-channel distributed feedback laser diode array (DFB-LDA) developed for the transmission of 100-Gb/s (10 × 10 Gb/s) signals separated by an 8 nm wavelength grid at a center wavelength of 1.55 μm. For the fabrication of this type of laser array, a selective area growth (SAG) technique, electron-beam lithography, and a reverse-mesa ridge waveguide LD processing technique were adopted to offer a tailored gain spectrum to each channel, providing both accurate lasing-wavelength control and excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…From this result, we confirmed that the degradations of various material and structural parameters related to the threshold current in a DFB‐LDA employing an SAG layer are significantly decreased by adopting a BH structure. In contrast, the slope efficiency (SE) is from 0.114 to 0.141 W/A at an injection current of 50 mA, which is about 0.02 W/A lower than 0.143–0.165 W/A of an RWG type described in [3]; however, the variation of SE was 0.027 W/A, which is similar to 0.022 W/A in [3]. The superimposed CW spectra of the eight channels are spaced at about 8 nm within 55.6 nm from 1528.4 to 1584 nm.…”
Section: Results Of Eight‐channel 10 Gb/s Dmlamentioning
confidence: 92%
See 2 more Smart Citations
“…From this result, we confirmed that the degradations of various material and structural parameters related to the threshold current in a DFB‐LDA employing an SAG layer are significantly decreased by adopting a BH structure. In contrast, the slope efficiency (SE) is from 0.114 to 0.141 W/A at an injection current of 50 mA, which is about 0.02 W/A lower than 0.143–0.165 W/A of an RWG type described in [3]; however, the variation of SE was 0.027 W/A, which is similar to 0.022 W/A in [3]. The superimposed CW spectra of the eight channels are spaced at about 8 nm within 55.6 nm from 1528.4 to 1584 nm.…”
Section: Results Of Eight‐channel 10 Gb/s Dmlamentioning
confidence: 92%
“…Specifications for a datacentre network were recently proposed and revised for a 100 Gb/s transmission of Ethernet signals over single mode fibre (SMF) with a distance of 2, 10, or 40 km [2]. We previously developed a ten‐channel 10 Gb/s distributed feedback laser diode array (DFB‐LDA) satisfying the above specifications by using selective area growth (SAG), E‐beam lithography, and reverse‐mesa ridge waveguide (RM‐RWG) LD processing techniques [3, 4]. However, for the fabricated LDA, the threshold current was shown to be 13–28 mA and the bias current appeared to be as high as 80–100 mA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMLs are becoming widely used in long-haul optical communication systems, but the technologies of wavelength division multiplexing (WDM) and high data rates per channel are now required in local area networks (LANs) such as passive optical networks (PONs) supporting 40 Gb/s [3]. There is therefore substantial interest in developing low-cost EMLs and WDM laser arrays to support higher data capacity in LANs [4], [5]. The operation of the EAM is based on the quantum confined stark effect (QCSE) and, in the so-called identical epitaxial layer (IEL) scheme, a common multi-quantum well (MQW) structure is used by both the laser and the EAM [1], [6].…”
Section: Introductionmentioning
confidence: 99%
“…For a laser array based on tunable lasers, Ishii et al demonstrated an integrated multi-wavelength array, which can cover 97 channels of a WDM system [41] . In 2014, a 100 Gb/s transmitter was realized by using a 10 × 10 Gb∕s hybrid integration DFB laser array with an array waveguide grating (AWG) [42] . A photograph of the integrated device is shown in Fig.…”
mentioning
confidence: 99%